2021
DOI: 10.1177/10499091211028820
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Palliative Prognostic Index in Predicting Survival Outcomes in Patients With Hematological Malignancies in the Acute Ward Setting

Abstract: Background: The palliative prognostic index (PPI) predicts the life expectancy of patients with terminally ill cancer in hospice settings. This study aimed to evaluate PPI as a prognostic tool for predicting the life expectancy of patients with hematological malignancies admitted to the acute ward. Methods: A total of 308 patients with hematological malignancies admitted to the hematological ward at a medical center between January 2016 and December 2017 were consecutively enrolled. PPI was scored within 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…42 Although PC prognostic indices can be used to predict life expectancy, they do not necessarily predict other outcome measures in HM such as likelihood of readmission. 43 Therefore, interprofessional discharge planning that involves PC integration could be beneficial to improve postdischarge quality measures. Although we did not directly examine additional value-based care measures such as cost or patient satisfaction, these could be assessed in future studies focusing on these important areas related to PC integration in caring for patients with HM.…”
Section: Jco Oncology Practice E691mentioning
confidence: 99%
“…42 Although PC prognostic indices can be used to predict life expectancy, they do not necessarily predict other outcome measures in HM such as likelihood of readmission. 43 Therefore, interprofessional discharge planning that involves PC integration could be beneficial to improve postdischarge quality measures. Although we did not directly examine additional value-based care measures such as cost or patient satisfaction, these could be assessed in future studies focusing on these important areas related to PC integration in caring for patients with HM.…”
Section: Jco Oncology Practice E691mentioning
confidence: 99%
“…16 Recent studies have reported the utility of PPI for predicting the life expectancy of patients with hematological malignancies. 17,18 It is interesting and important that this study suggested the utility of PPI for end-of-life prognosis not only in advanced hematological malignancies but also in the chemotherapy group. Moreover, it has been suggested that inflammationbased prognostic scores, such as GPS, PNI, and CONUT, are related to survival in hematological malignancies as predictors of the prognosis of chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…Most were conducted in palliative care units/team consultations ( n = 20), followed by hospices ( n = 8), mixed settings ( n = 5), acute wards ( n = 4) and home/community palliative care settings ( n = 2) (Table 1). Most PPI assessments were conducted by doctors only, nurses only 24,66,83 or both. 53,60,62,76 The PPI was used to predict numerous survival durations.…”
Section: Resultsmentioning
confidence: 99%